2001
DOI: 10.1046/j.1523-1755.2001.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces MCP-1 expression partly via tyrosine kinase–AP-1 pathway in peritoneal mesothelial cells

Abstract: : High glucose induced mesothelial MCP-1 expression partly via the tyrosine kinase-AP-1 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 36 publications
4
36
1
Order By: Relevance
“…Inflammatory cytokines and growth factors, such as platelet-derived growth factor (PDGF) and interleukin-1, can trigger the expression of MCP-1 through activation of several signalling pathways such as extracellular signal-related kinase (ERK)1/2 [2], p38 mitogen-activated protein (MAP) kinase [3], protein kinase C [4], activator protein (AP)-1 [5] and nuclear factor (NF)-kB [6]. We have reported that integrin-mediated activation of intracellular signalling molecules also induces MCP-1 expression in mesangial cells [7], suggesting that abnormal remodelling of ECM observed in many types of glomerular diseases can upregulate MCP-1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cytokines and growth factors, such as platelet-derived growth factor (PDGF) and interleukin-1, can trigger the expression of MCP-1 through activation of several signalling pathways such as extracellular signal-related kinase (ERK)1/2 [2], p38 mitogen-activated protein (MAP) kinase [3], protein kinase C [4], activator protein (AP)-1 [5] and nuclear factor (NF)-kB [6]. We have reported that integrin-mediated activation of intracellular signalling molecules also induces MCP-1 expression in mesangial cells [7], suggesting that abnormal remodelling of ECM observed in many types of glomerular diseases can upregulate MCP-1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that fish oil reduces NF-B activation, inflammation, and renal damage in a salt-sensitive model of hypertension, an effect that is only in part due to reduction in blood pressure (16). A number of in vitro studies implicated activation of ERK, NF-B, and/or AP-1 in the transcriptional regulation of MCP-1 in response to a variety of proinflammatory cytokines (38,43,46,47,52,73,79).…”
mentioning
confidence: 99%
“…In addition to renal fibrosis, MCP1 is also implicated in the pathogenesis of peritoneal fibrosis. In peritoneal fibrosis, it has been suggested that high glucose concentration in conventional peritoneal dialysis solutions, which are used for continuous ambulatory peritoneal dialysis, plays a role in fibrotic lesions by increasing MCP1 gene expression (5,6).…”
mentioning
confidence: 99%